Effects of Authentication of Users in Mobile Internet Protocol Version 6 - Obenofunde, Simon Tabi (2004)
User security in the Internet has generally been well taken care of at the application layer. Judging from the mobility and portability of a mobile terminal and its ability to get connected to the Internet while away from home, it becomes necessary to be sure of who is using that terminal. Presently, mobility is difficult, if not impossible to detect at the application layer though easily detectable at the network layer. Therefore it becomes necessary to apply the application layer solution to the network layer. In this thesis, a user authentication program is modeled and simulated using Network simulator2 (NS2). Various network topologies are simulated in order to investigate the effects of implementing this program on a network for various network performance parameters. The results are stored in trace files. Tracegraph201 is used to generate plots, from which data is extracted and then plotted again using Excel for comparison purposes. In this thesis, we measured the throughput against simulation time, and then the delay against throughput and event time. Comparisons are done between systems implementing authentication and those that do not. The results show that the average delay is not much affected by the implementation of the program. The network performance is greatly affected by the number .of packet present in the network at any given time. Nevertheless, throughput is much improved at the detriment of bandwidth, as seen fiom the number of dropped packets. Thus, it. is recommended that user authentication be applied to mobile Internet Protocol version 6 (IPv6) as a security measure. The conclusions made above are based purely on simulation results. The password system is also recommended as a viable solution for this authentication as its implementation is most convenient for mobile users. A password algorithm is proposed from which a program can be written in any language deemed suitable.